Profitability of storage hedges for Kansas wheat producers - Ward, Lacey L. (Kansas State University, 2015)
Hard Red Winter Wheat is an extremely important part of the Kansas agricultural industry. In Kansas, this type of wheat is planted in the fall and harvested in mid-June. After harvest, producers have the option to either store or sell their wheat. If they decide to store, the wheat can be stored on-farm or in a commercial facility. Another storage decision is whether to store the wheat hedged or unhedged (speculative) storage. Hedging is a technique to limit the price risk associated with selling or buying commodities. This study compared hedged and speculative decisions for both on-farm and commercial storage scenarios for 108 locations geographically dispersed across Kansas. Wednesday prices were gathered for each location during the 10-year time period from 2004 to 2013. All monthly storage period possibilities from July to May were examined to determine the storage returns potential. All results are displayed as the profit or loss achieved compared to selling in June at harvest. Averages for Kansas were negative or slightly positive for all storage scenarios, but hedged returns showed much less variability in results compared to speculative returns. Regional differences showed that North Central Kansas displayed the highest level of basis improvement over the 10-year period followed by South Central Kansas. A regression analysis using nearby basis in June, harvest price, and futures contract spreads as independent variables and storage returns as a dependent variable showed emphasis on the futures spread having the biggest influence on storage profits.
Keywords: Wheat; Marketing; Storage; Hedging; Grain; Kansas; Agriculture, General (0473); Economics, Agricultural (0503)